EFL Teachers’ Challenges and Strategies in Managing Delinquent Students - Aprilia Indah Wulandari; Ferra Dian Andanty (Journal on Education, 2023)
The present study aims to describe the challenges and strategies in managing delinquent students by English teachers in Islamic senior high school in a sidoarjo. This is done to find out the challenges of the teachers and the strategies they use to overcome these challenges. This research was conducted by using qualitative method with a case study as a qualitative design. The primary data was the statements taken from two teachers’ interview and Supportive data taken from observation. The data collection techniques in this research were unstructured interview and natural observation. The technique of analysis in this research was thematic analysis. Based on the data collected, the researchers found that there were four challenges faced by teachers, namely (1) unequal attention, (2) unequal interaction, (3) students were not active, and (4) wayward student. The strategies used by the teacher to overcome these challenges (1) praising unobedient students, (2) managing students, (3) changing student seats, and (4) using work groups. From these conclusions, the researcher offers several suggestions for dealing with the challenges faced by teachers. Teachers should use more creative strategies in developing various activities, making learning media. Regarding creativity teachers employed various mediums to make it easier for pupils to acquire and grasp the topic. Audio, visual, and audiovisual media were examples of media. Audio and visual media were the most commonly employed in ELT classes. The planning and creativity teachers become the main factors to make the class more interactive using several media.